ANALISIS PUTUSAN NOMOR 24/PID.PRA/2018/PN.JKT. SEL TENTANG PUTUSAN HAKIM MENGENAI PENETAPAN STATUS TERSANGKA BARU DI PRAPERADILAN - Vika Anggraini; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Pretrial is a judicial institution that only has authority limited to deciding whether the arrest or detention is valid or not, termination of the investigation, termination of prosecution, including compensation or rehabilitation for someone whose case has been terminated. But in judge Effendi Mukhtar decision as a single judge in a pretrial case Number 24 / Pid.Pra / 2018 / PN.Jkt.Sel dropped a verdict in which one of the contents stated